If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+2*6=17
We simplify the equation to the form, which is simple to understand
x+2*6=17
Simplifying:
x+12=17
We move all terms containing x to the left and all other terms to the right.
+1x=+17-12
We simplify left and right side of the equation.
+1x=+5
We divide both sides of the equation by 1 to get x.
x=5
| -6m-21=0 | | 5=10-2t | | 5x=-6x+44 | | h=65t-5t^2 | | -13(n-83)=n+4 | | 2(25+4)+2(25)=108 | | 3xy-x^2+4yx+5x^2-3= | | h=652-5t^2 | | .125h=-8 | | 3m-9n=9 | | -8m=-72 | | A=(-3+10x)-(-8x-4) | | 5x^2-5ax-60a^2=0 | | -3x-5=4x+9 | | -2(-4)(-4)= | | 204=18-x | | 204=18+x | | 108=4+x | | x^6-729=0 | | -7x^2+7x+14=0 | | 2x^4-2x^3+2x-2=0 | | x^2+x+72=0 | | P^2+2y-2=0 | | 2a*a= | | x^2+2x=-20 | | (5x+8y)(5x+8y)= | | -12x=-444 | | 18+x=204 | | Y^2-4y+2=0 | | (-2)+4-(-6)= | | -1/9(x-27)+1/3(x+3)=x+4 | | graph-3x-6y=6 |